A NOTE ON INTRA-ELEMENTAL ISOTOPE EFFECTS AND THE INTERPRETATION OF NON-MASS-DEPENDENT ISOTOPE VARIATIONS - Deines P. (My University, 2003)
Significant deviations from the ''normal'' intra-elemental isotope fractionation relationship for sulphur isotopes can be caused by isotope exchange by equilibria involving gaseous S2 and H2S. The phenomenon applies to other elements and it is caused by differences in the crossover temperature of isotope exchange reactions for the different (at least three) isotopes of an element.
Keywords: INTRA-ELEMENTAL ISOTOPE EFFECTS; CROSSOVER TEMPERATURE; NON-MASS-DEPENDENT ISOTOPE